Analysis of vulnerability to facebook users - Hanne, Michelle; Silva, Cristiano; Almeida, Jussara; Gonçalves, Marcos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Facebook, the largest social network nowadays currently has 901 million active users, with 526 million of them accessing the system daily. With a very rapid growth, Facebook has become a potential site for the collection of personal information by unauthorized individuals, leaving its users vulnerable to actions of violation of privacy, spamming and phishing. This article discusses the vulnerability of Facebook users based on their exposure in the network. To this end, we propose a numerical indicator capable of estimating the degree of vulnerability of each user. This indicator is a function of both the amount of personal content published by the user and the size of her network. We demonstrate the use of the proposed indicator in real data collected from 75,000 Facebook users.